2000
DOI: 10.1023/a:1006325929424
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Topotecan Combined with Various Active G2/M-Phase Anticancer Drugs in Human Tumor-Derived Cell Lines

Abstract: Topotecan (TPT) is a DNA-Topoisomerase I poison that exhibits antitumor activity. TPT, like other DNA-damaging agents, arrests or delays cell cycle progression during S- and G2-phase in a wide variety of tumor-derived cell lines. Particularly, the G2-arrest gives time for the cell to repair its DNA lesions prior to starting a new cell cycle. Based on these observations, we assessed the interaction between TPT and G2/M-active agents in p53-mutated cell lines of diverse origin in order to achieve cell toxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Furthermore, a large number of studies in the literature [42][43][44][45] have reported that small molecule drugs that induce G2/M phase arrest could eventually induce tumour cell apoptosis. However, aer Hela cells were treated with 4, little apoptosis was observed (Fig.…”
Section: Cellular Localizationmentioning
confidence: 99%
“…Furthermore, a large number of studies in the literature [42][43][44][45] have reported that small molecule drugs that induce G2/M phase arrest could eventually induce tumour cell apoptosis. However, aer Hela cells were treated with 4, little apoptosis was observed (Fig.…”
Section: Cellular Localizationmentioning
confidence: 99%
“…In vitro data has shown this combination may have synergistic effects on tumor death [43,44]. Docetaxel may have the greatest synergistic effects with topotecan when given at the time of highest topotecan-induced G 2 -phase cell arrest [45]. Both of these drugs are also metabolized by the CYP 3A4 system, possibly potentiating toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale that supports the combination of irinotecan and oxaliplatin is well described in experimental studies [20, 21], moreover the lack of overlapping toxicity profile made it necessary to evaluate this regimen in the clinical practice. Various phase I trials have been recently published using either a weekly, biweekly or 3-weekly administration schedule of irinotecan [16, 17, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…This sequence has a cytokinetic base, since the topoisomerase I inhibitor is phase specific and it can be expected to have an optimal effect on proliferating cells. It has been demonstrated that, when administered before oxaliplatin, irinotecan generates earlier apoptosis and leads to the induction of greater necrotic cell death than that obtained when it is administered after oxaliplatin [20, 21]. Using the sequence of irinotecan followed by oxaliplatin, we intended to favor the more specific action of irinotecan in CRCs with the aim of achieving a possible advantage in terms of tolerability, although we utilized a higher dose compared to other previous studies [16, 19].…”
Section: Introductionmentioning
confidence: 99%